Perkembangan Ilmu Filsafat di Dunia Pendidikan - Mardinal Tarigan; Winda Khofifah; Novi Yanti; Sabila Kamalia; Azura Azura (Universitas Dehasen Bengkulu, 2022)
Philosophy plays a very important role in human thinking to build knowledge. Philosophy digs and everything about nature as deep and deep as possible. In this case, it is conceivable that philosophy is the source of all science and knowledge. Philosophy contributes to the study of what kind of processes will be known by people who use knowledge. Philosophy or thinking Knowledge is necessary because thinking and knowing are two things. What are the characteristics of humans? What do you know about the process? Thinking becomes knowledge. Knowledge is information that has been done Paired with understanding and possible action, then embedded in one's heart. Knowledge has the following predictive power: Results recognize patterns. Therefore, efforts to change attitudes and behavior Efforts to mature people through individuals or groups and education and training efforts are referred to as opportunities to change traditional social patterns to more modern thinking patterns.